Numerical Analysis of the Relationship between Nasal Structure and Its Function - Shen Yu; Xiu-zhen Sun; Ying-xi Liu (The Scientific World Journal)
The functions of the nasal cavity are closely related to its structure. In this study the three-dimensional finite element models were established based on the clinical data of twenty-four volunteers to study the influence of nasal structure on nasal functions of heating the inhaled airflow. Numerical simulations mainly concerning the airflow distribution and the airflow temperature are performed. The character of airflow heating process in these models is gained from the simulation results of these nasal cavities. The parameters describing the geometry of nasal cavity, such as the surface area of nasal airway and the volume of nasal cavity, are considered to be related to the nasal function of heating the inhaled airflow. The approximate function describing the relationship between the geometric parameters of the nasal airway and the nasal functions is gotten. This study can provide a numerical platform for studying some clinical problems and will contribute to the further research on the relationship between nasal structure and nasal functions.